EFFECTIVENESS OF STATIC THYRISTOR COMPENSATORS SYSTEMS ON THE EXAMPLE OF OJSC «BSW» - A. I. Rozhkov; A. I. Rozhkov; V. V. Logvin; A. V. Kozlov; O. M. Grudnitsky; A. V. Feklistov (Литьë и металлургия, 2017)
The issues of technical and cost efficiency of system of statistical thyristor compensators on the example of the Belarusian steel works are considered. Information on researches of system of power supply of arc-furnace melting shops is provided. The data of the highest harmonicas of the arc steel-melting furnace and ladle furnace are specified. The diagrams of current, voltage, capacities during the operation of the arc steel-melting furnace both with system of thyristor compensators, and without it are provided.